Special issues relating to corporate governance and family control - Morck, Randall 1986- (Policy research working paper, 2004)
"Control of corporate assets by wealthy families in economies lacking institutional integrity is common. It has negative implications on corporate governance and adverse macroeconomic effects when it extends across a sufficiently large part of the country's corporate sector. Morck and Yeung consider the reasons why family control and control pyramids predominate in emerging market economies and in some industrial economies. They also discuss the reasons why widely held freestanding firms predominate in the United States. The authors discuss policies that countries might adopt to discourage family control pyramids, but caution that control pyramids are but one feature of an institutionally deficient economy. A concerted effort to improve a country's institutions is needed before diffuse ownership is desirable. This paper a product of the Global Corporate Governance Forum, Corporate Governance Department is part of a larger effort in the department to improve the understanding of corporate governance reform in developing countries"--World Bank web site